Mechanical, fracture toughness, and fatigue behavior of spinifex littoreus fiber on echinoidea‐spike toughened epoxy composite. Issue 4 (15th February 2022) - Senthil Kumar, S.; Anil Kumar, T. CH; Chokkalingam, Mohan; Kaliappan, S.; Boopathi, S.; Srinivas, Chidurala; Patil, Pravin P.
Abstract: Novel spinifex littores fiber‐reinforced echinoidea spike particle dispersed epoxy resin hybrid composite has been prepared and characterized. The main objective of this research work was to prepare a new system of epoxy hybrid composite comprises of surface‐treated novel spinifex littores fiber (SLF) and echinoidea spike powder (ESP) for sustainable material development. The fiber was treated with alkali and silane for effective adhesion with matrix. The composites were prepared using hand layup method and post cured at 120°C. The mechanical properties were improved with increasing particle content. The wear result shows a lowest coefficient of friction and sp. wear rate of 0.43 and 0.004 mm 3 /Nm for SP5 composite designation. Fracture toughness of 32.1 ± 0.69 MPa √m and energy release rate of 1.257 ± 0.071 mJ/m 2 was observed for composite designation SP4. A highest fatigue life count of 26, 832 was observed for composite contains 1 vol% of silane‐treated ESP and 8 h alkali cum silane‐treated SPF. The fractographs reveals toughness improved matrix phase via shear cup formation. These marine based eco‐friendly reinforcement based epoxy composites could be used in various applications in the cadre of automobile, mini‐aircrafts, structural, sports, and domestic. Abstract :